THE CORRELATION BETWEEN STUDENTS’ PHONETIC SYMBOLS MASTERY AND PRONUNCIATION ABILITY AT TRIDINANTI UNIVERSITY (English Community Journal, 2023)
Pronunciation is one of the subjects that should be accomplished by EFL students at Tridinanti University. Surely, the mastery of English phonetic symbols may have the relation to the pronunciation ability. Hence, the objectives of this study were (1) to dig out the information whether or not there was a significant correlation between EFL students of Tridinanti University’ phonetic symbols mastery and their pronunciation ability and (2) to find out how much the students’ phonetic symbols mastery contribute toward pronunciation ability. The method used in this research was correlation design. There were 50 students as the population of this research, and the researchers took 34 students as the sample of this study using purposive sampling technique. This research data were analyzed using Pearson Product Moment formula to know whether there was a correlation between students’ phonetic symbols mastery and pronunciation ability. There were two instruments of tests, they were phonetic test and pronunciation test. Based on the result, it was found that the pearson correlation coefficient was 0.466. It can be concluded that there was a fair correlation between students of EFL Tridinanti University’s phonetic symbols mastery and their pronunciation ability. The value of R Square in regression analysis was 0.218. It can be assumed that the students’ phonetic symbols mastery contribute as much as 21.8% toward pronunciation ability.